The development of ethnoscience-based e-student worksheets to enhance Students scientific literacy at Madrasah Ibtidaiyah - Wiratama, Rivaldi; Minarno, Eko Budi; Tharaba, M. Fahim (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
Science literacy is the ability to apply scientific knowledge in daily life, yet students' science literacy in Indonesia remains low. This study aims to develop ethnoscience-based electronic student worksheets (e-LKPD) and evaluate their feasibility, attractiveness, and effectiveness. The research uses the Research and Development (R&D) method with the ASSURE development model. The results show that the e-LKPD received validation from three experts: material experts (95.55%), design experts (91.66%), and learning practitioners (83.00%), all falling into the very valid category. The worksheets were found to be highly attractive, with a score of 85.21%. The N-Gain score was 0.79, indicating high effectiveness. The independent sample T-test revealed a significant difference in science literacy between the experimental and control classes (p = 0.001, less than 0.05). In conclusion, ethnoscience-based e-LKPD effectively enhances students' science literacy, as shown by the improvement from pretest to posttest results.